Structural and electronic properties of bulk GaP and AlP and their (GaP)n / (AlP)n superlattices - M., Merabet; S., Benalia; D., Rached; A., Bouhemadou; S., Omran; Ali H., Reshak; M., Rabah (Elsevier Ltd., 2011)
Link to publisher's homepage at www.elsevier.com